2017
DOI: 10.1192/bjpo.bp.116.004077
|View full text |Cite
|
Sign up to set email alerts
|

Gestational vitamin D deficiency and autism spectrum disorder

Abstract: BackgroundThere is growing interest in linking vitamin D deficiency with autism spectrum disorders (ASDs). The association between vitamin D deficiency during gestation, a critical period in neurodevelopment, and ASD is not well understood.AimsTo determine the association between gestational vitamin D status and ASD.MethodBased on a birth cohort (n=4334), we examined the association between 25-hydroxyvitamin D (25OHD), assessed from both maternal mid-gestation sera and neonatal sera, and ASD (defined by clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 37 publications
3
87
1
1
Order By: Relevance
“…A much larger ( n = 4,229) cohort study showed an association between vitamin D deficiency measured at mid‐gestation and in cord blood and autism‐related traits [Vinkhuyzen et al, ], but the association with cord blood vitamin D deficiency appeared to be driven primarily by those who had deficiencies at both time points. Similarly, in the same cohort ( n = 4,334), vitamin D deficiency in cord blood was not associated with ASD diagnosis, while low maternal mid‐gestation 25(OH)D was associated [Vinkhuyzen et al, ]. Taken together, these studies and a study that found low maternal first trimester 25(OH)D was associated with higher risk for ASD diagnosis [Chen et al, ], suggest that there may be a critical period for gestational vitamin D and ASD earlier in pregnancy, that was not well‐measured in this study.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…A much larger ( n = 4,229) cohort study showed an association between vitamin D deficiency measured at mid‐gestation and in cord blood and autism‐related traits [Vinkhuyzen et al, ], but the association with cord blood vitamin D deficiency appeared to be driven primarily by those who had deficiencies at both time points. Similarly, in the same cohort ( n = 4,334), vitamin D deficiency in cord blood was not associated with ASD diagnosis, while low maternal mid‐gestation 25(OH)D was associated [Vinkhuyzen et al, ]. Taken together, these studies and a study that found low maternal first trimester 25(OH)D was associated with higher risk for ASD diagnosis [Chen et al, ], suggest that there may be a critical period for gestational vitamin D and ASD earlier in pregnancy, that was not well‐measured in this study.…”
Section: Discussionmentioning
confidence: 50%
“…Animal studies show long‐lasting neurodevelopmental effects of transient vitamin D deficiency during gestation leading to autism‐relevant structural and functional changes in the brain and behaviors of the offspring [Eyles et al, ; Eyles et al, ; Grecksch, Ruthrich, Höllt, & Becker, ; Levenson & Figueiroa, ]. Several studies have recently found associations between gestational vitamin D status and ASD diagnosis [Chen, Xin, Wei, Zhang, & Xiao, ; Fernell et al, ; Vinkhuyzen et al, ] and autism‐related traits [Vinkhuyzen et al, ], but findings have been inconsistent, and the number of children diagnosed with ASD has been relatively small and did not allow for investigation of effect modification by race and sex. There is biological potential for heterogeneous effects across sex given that sex hormones like estrogen and testosterone have very different effects on calcitriol's metabolism [Cannell, ], and males are more prone to vitamin D deficiency [Tonnesen, Hovind, Jensen, & Schwarz, ].…”
Section: Introductionmentioning
confidence: 99%
“…has been implicated with both psychotic and affective disorders [16][17][18][19][20][21][22] and since it acts as an epigenetic regulator during neurodevelopment, it has the potential to integrate intrinsic and environmental signals into the shaping of the maturing brain. Here, we demonstrate that 74 and autism spectrum disorder 75,76 ), and genome wide association of loci harboring the RXRG in bipolar disorder 77 and attention deficit hyperactivity disorder 77 , LXRA in autism spectrum disorder 78 , and NR4A2 in major depressive disorder 79 . Gene set and pathway analyses of GWAS data in major depressive disorder and bipolar disorder additionally reveal enrichment of genes implicated with thyroid hormone and retinoic acid signaling 60 as well as genes containing RAR/RXR consensus sequences 79 .…”
Section: Discussionmentioning
confidence: 61%
“…Accordingly, Vinkhuyzen et al [81] also showed an association between both mid-gestational and neonatal vitamin D deficiency [25(OH)D concentration less than 25 nmol/L] with autism-related traits at 6 years of age in a large Dutch population-based birth cohort. Moreover, mid-gestation vitamin D deficiency was associated with a higher risk of being diagnosed with clinical ASD [82]. DOI: 10.1159/000487370 In summary, the current evidence indicates that prenatal vitamin D status may impact the risk of ADHD symptoms and ASD later in life; however, the evidence for other neurobehavioral problems is still inconsistent.…”
Section: Autism Spectrum Disordermentioning
confidence: 96%